نموذج وحدة تدريسية في مهارة القراءة لطلبة القانون الشرعي غير الناطقين باللغة العربية = A module of syllabus design in reading skill for teaching Arabic for the learners of Islamic law non-native speakers - Ali, Asem Shehadeh Saleh; Ibrahim Isa, Mahmud Abdul Fattah (Jerash University, 2019)
يسعى هذا المقترح إلى تصميم وحدة لتعليم اللغة العربية لطلبة القانون الشرعي غير الناطقين بها، وهم الطلبة المنخرطون ي دراسة القانون الشرعي بكلية القانون بالجامعة الإسلامية العالمية بماليزيا؛ حيث قررت اللغة العربية لهؤلاء الطلبة بوصفها متطلباً جامعياً يسعى إلى ربط الطالب الجامعي باللغة العربية قراءة، وكتابة، وتحدثًا. ويهدف هذا المقترح إلى تمكين الطالب الجامعي من القراءة السليمة الخالية من الأخطاء، وتحديد الأفكار الرئيسة للنص، فضلاً عن إقامة الحجج وإبداء وجهات النظر، وفهم النصوص القانونية بصورة تعكس رؤيةً واضحةً، وقدرةً على عرض الموضوع، وتوظيف المعرفة اللغوية بأساليبها التركيبية والبلاغية ي فهم النصوص القانونية ومصطلحاتها. وتوصلت الدراسة إلى أن اللغة العربية مهمة لفهم مواد القانون الشرعي؛ حيث إن مصادر التشريع باللغة العربية، وهناك حاجة ماسة لطلبة القانون الشرعي إلى منهج ذي طبيعة خاصة لفهم مواد القانون الشرعي بصورة أعمق، ووجوب توفير منهج للارتقاء بمهارة القراءة لطلبة القانون الشرعي، للتمكن من مواد القانون الشرعي، والحاجة كذلك إلى منهج يعالج النصوص الفقهية والشرعية بصورة متدرجة أمر اجمعت عليه الغالبية العظمى من عينات الاستبانة، وإلزام الطلبة بمنهج للارتقاء بمهارة القراءة فيما يتعلق بمواد القانون الشرعي لمدة لا تزيد عن عام بجانب المواد الدراسية، كان أمراً أجمع عليه أغلب عينات الاستبانة. ********************************************************** This paper tries to propose a syllabus design for teaching Arabic to university students who are not specializing in the language with special reference to the students of Petroleum College of Abu Dhabi. They are engineering students who have to fulfill the college requirement subject of Arabic that covers the reading, writing and conversation skills. The syllabus aims to enable the students to read correctly, identify the main ideas of the text, argue and state opinions, write a cohesive text that clearly reflects the idea, be able to present the topic, use linguistic knowledge with the structural and rhetorical styles in producing written text, apply linguistic knowledge in analyzing the writing of others with correct use of language and styles. The study discovered the need to set up such syllabus to teach Arabic specifically to non-specialist students in Arabic; the need analysis had also helped the students to give input on their own expectations; non-specialist students are in a more need to the Arabic language skills comparing to the others; they need more practical use of the language then the knowledge about the language and the material content need to made relevant with the reality of the student life.